Beyond Nonmarket Strategy: Market Actions As Corporate Political Activity - Funk, Russell J.; Hirschman, Daniel (Academy of Management Review, 2017)
Many firms attempt to manage their legal and regulatory environments by influencing policy makers. Typically, researchers have focused on how firms use nonmarket actions, including lobbying, campaign contributions, and related activities, to gain policy influence. We argue that firms may also attempt to change the effects of policies through market actions. Market actions may lead to both formal policy change (i.e., transformations of codified rules) and interpretive policy change (i.e., transformations of the effects of rules without changes in their codified form). We identify two pathways by which firms’ market actions may produce interpretive policy change: implementation and innovation. Implementation-driven change occurs when firms’ interpretations of incomplete laws alter and clarify the meaning of those laws. Innovation-driven change occurs when firms engage in novel activities that are difficult to interpret within existing regulatory frameworks and, thus, alter the effects of those regulations. We then theorize how firms’ market actions may complement traditional, nonmarket political mobilization in an analysis of sequences of formal and interpretive policy change.